2011
DOI: 10.5812/kowsar.1735143x.776
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Transforming Growth Factor-β1 Gene Polymorphisms Among Iranian Patients With Chronic Hepatitis C

Abstract: BackgroundChronic hepatitis C infection is caused by the hepatitis C virus (HCV), and its clinical complications include liver cirrhosis, liver failure, and hepatocellular carcinoma.Transforming growth factor-β1 (TGF-β1) is an important cytokine in cell growthand differentiation, angiogenesis, extracellular matrix formation, immune responseregulation, and cancer development and progression.ObjectivesThe aim of this study was to investigate the relationship between single nucleotide polymorphisms (SNPs) in TGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…Recently, Romani et al (2011) analyzed a possible link between +915G/C, -509C/T, +869T/C polymorphisms and chronic HCV infection in Iranian population. They could not find any association between studied factors ( 21 ).…”
Section: Discussionmentioning
confidence: 85%
“…Recently, Romani et al (2011) analyzed a possible link between +915G/C, -509C/T, +869T/C polymorphisms and chronic HCV infection in Iranian population. They could not find any association between studied factors ( 21 ).…”
Section: Discussionmentioning
confidence: 85%
“… 41 Recently, Ramos et al, 29 in addition to examining an association with IL-28B polymorphisms, reported the participation of IL-10 (−1082) GG and IL-4 (+3) CT genotypes during acute hepatitis C with viral clearance. We failed to find an association with these cytokines, but the controversy regarding cytokine polymorphisms and CHC 42 44 encourages us to continue studying the influence of host polymorphisms and hepatitis C outcomes. Recently in a similar article, Pasha et al 45 reported that IL-28B, TGF-β1 (−509), and TNF-α (−308) polymorphisms that appear to influence cytokine production may be host genetic factors associated with HCV genotype 4 infection susceptibility and response to combined antiviral treatment, demonstrating the importance of host genetic factors in HCV infection outcome.…”
Section: Discussionmentioning
confidence: 90%
“…Romani et al concluded that SNPs in the TGF-β1 gene cannot be used as prognostic factors for HCV infection in an Iranian population, despite the possibility that most of the population is susceptible to HCV infection. 44 However, the functionally relevant TGF-β1 polymorphism (GG) at codon 25 may play a role in the rapid development of HCV-induced graft fibrosis, and the presence of the C allele in addition to younger donor age, female sex of the recipient, and HCV genotype other than 1b seems to protect against the development of advanced stages of fibrosis. 50 …”
Section: Discussionmentioning
confidence: 99%
“…In a different tune, Kimura et al have demonstrated − 509C allele to be associated with a higher clearance rate of HCV as well as with lower promoter activity ( Kimura et al, 2006 ). However, in the contest of hepatitis B and Iranian patients, absence of association between TGF-β1 − 509C > T and + 915G > C polymorphisms with chronic hepatitis B indicated that these changes do not play a significant role in increasing the risk of chronic infection in Iranian patients ( Razavi et al, 2014; Romani et al, 2011 ). Our finding of TGF-β1 polymorphism at position − 509 with increase in C > T genotype in the patient group suggests its protective role, since all the patients recovered.…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping of the 3 SNPs in the TGF-β1 gene (− 509C > T, + 869T > C and + 915G > C) reported to be associated with alteration in plasma TGF-β1 levels ( Fig. 1 a) was performed using polymerase chain reaction-restriction fragment length polymorphism (PCR–RFLP) method ( Romani et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%